English teachers’ attitudes toward their new roles promoted by English-as-an-international-language pedagogy - Muhammad Rahimi; Maryam Pakzadian (Indonesian TESOL Journal, 2019)
Teaching English as an International Language (EIL) has gained significant ground in recent years. However, the successful implementation of EIL pedagogy largely depends on teachers’ attitude toward EIL. As such, exploring teachers’ attitudes toward principles of EIL pedagogy is of paramount significance. To this end, we examined teachers’ attitudes toward their new roles promoted by principles of EIL pedagogy. Four major findings emerged. First, teachers still consider native accent the correct model. Second, participants were not aware of their role as promoters of intercultural competence, and culture was not a planned part of the curriculum. Third, the teachers were mostly passive consumers of commercial textbooks instead of being critical users of instructional materials. Fourth, the majority of participants were not critical users of teaching methodologies. The implications of our findings for language teacher education in the contexts of EIL are also discussed.